Emotional regulation and Arnold’s self-ideal: a way to flourishment - Ruiz-Fuster, Fátima; Bernal-Martínez de Soria, Aurora; Echavarría, Martín F. (Frontiers in Psychology, 2024)
The convergence of researchers in the fields of flourishing, moral psychology, and social–emotional studies has reached a stage where developing a theory that connects emotional regulation and flourishing is meaningful. This theoretical investigation aims to uncover insights from the research of Magda B. Arnold, renowned for her theory of emotions, and lesser-known for her notion of the self-ideal, regarding the relationship between emotional regulation and flourishing. Our initial hypothesis posits that Arnold’s concept of self-ideal provides a framework for understanding how to foster emotional regulation in individuals by directing it toward constructive life objectives. To achieve this, we explore the current state of emotional regulation and flourishing and the relationship between these concepts; we consider the interconnectedness of emotion and self-ideal within Arnold’s theory and analyze its potential to serve as a foundation for building a theory relating flourishing and emotional regulation. We find in Arnold’s theory substantial ideas about the relationship between emotional regulation, flourishing, and self-ideal, as well as emerging empirical research relating to these themes. We conclude that Arnold’s research can serve as a catalyst for developing psychological intervention models that enhance emotional regulation and promote a flourishing life.